Polyamorphism of Amorphous SiO₂ under Compression Based on Two-State Model - Luyen, Thi San; Nguyen, Van Hong (Old Journal, 2019)
Microstructure and polyamorphism of amorphous SiO₂ at 500 K and 0+20 GPa were investigated by molecular dynamics simulation. The results indicate that in the studied pressure range, the network structure of amorphous SiO₂ includes SiOₓ structure units (x = 4, 5, 6) and OSiᵧ (y = 2, 3). The two-state model (high density and low density) is used to describe the network structure of the amorphous SiO₂. High-density phase is formed by SiO₅ and SiO₆ linked via OSi₃, low-density phase is formed by SiO₄ linked via OSi₂. The proportion of high density phase and low density phase depend on pressure.